A preliminary multidisciplinary design procedure for tactical missiles. (July 2019) - Khalil, Mostafa; Hashish, Anwer; Abdalla, Hamed M
During missile system development, multidisciplinary design procedure is iteratively implemented based on the missile objective and target nature including internal ballistic, warhead function, and airframe configuration. By applying missile preliminary design, a good estimation for different design parameters can be obtained which will be useful through further detail design process. The aim of this paper is to build a preliminary design procedure for an unguided tactical missile that uses single-stage solid propellant motor to deliver a defined payload mass to a desired ground range. Based on data of available similar mature missile systems, two empirical formulas are developed to serve in the initial sizing of the missile with consideration of slenderness ratio, warhead mass, and desired ground range. Two different design concepts are implemented for tubular and star grains with different propellant compositions and chamber filling coefficients while the body-alone airframe configuration is adopted. The results demonstrate the capability of the proposed design procedure in defining the detailed design parameters. The impact of changing the propellant compositions and chamber filling coefficients on the obtained ground range is also explored.